Гейміфікація у навчальних платформах: вплив на мотивацію та ефективність навчання - Медведєва, Г. М.; Дейнеко, Ж. В. (ХНУРЕ, 2025)
The present paper is devoted to the investigation of gamification in educational platforms and its impact on student motivation and learning effectiveness. The work discusses the implementation of such game mechanics as points, badges, levels, and leaderboards and their influence on students’ engagement and knowledge retention. Moreover, the article contains the discussion of the issues and challenges related to the adaptation to various learning styles and student competencies. The research also provides the summarized information concerning the benefits and drawbacks of gamification and discusses the necessity to study further its long-term effect and implementation patterns in different learning settings.
Keywords: гейміфікація у навчальних платформах; ефективність навчання